Increased task-induced mental fatigue in problematic Internet Use: an fMRI study - Ákos Arató; Anna Tímea Szente; András Matuz; Eszter Áfra; Husamalddin Ali Alhour; Gábor Perlaki; Gergely Orsi; Gréta Szabó; Barnabás Dudás; Szilvia Anett Nagy; Norbert Kovács; Árpád Csathó; et al. (Computers in Human Behavior Reports, 2025)
According to recent research, the level of problematic Internet use (PIU) is associated with chronic mental fatigue. In contrast to chronic fatigue, the association between PIU and task-induced fatigue has not been investigated. Based on previous scientific work, it is conceivable that task-induced subjective fatigue and PIU may share a common neurological background. Therefore, investigation of the association between them is indispensable. We used the Psychomotor Vigilance Task to induce fatigue and functional magnetic resonance imaging (fMRI) to investigate changes in the blood-oxygen-level-dependent (BOLD) signal during the task, and a self-reported questionnaire to assess PIU. We found that the extent of PIU predicted subjective mental fatigue changes during the task. Task-induced changes in the BOLD signal in the left precuneus, and in the left medial, middle, and superior frontal gyri correlated negatively with the PIU level. In addition, task- and PIU-related changes in the BOLD signal within these areas were negatively associated with the changes in subjective mental fatigue. Our findings highlight the association between PIU and task-induced subjective mental fatigue.